Design and Implementation of Sustainable Transportation- Electrical Velomobile (International Journal of Scientific Research in Science and Technology, 2024)
Velomobiles exemplify a cutting-edge solution for sustainable transportation, merging design, efficiency, and eco-friendliness. These human-powered vehicles combine the benefits of bicycles with a streamlined, enclosed structure, offering a practical alternative to traditional transport. Constructed from lightweight materials like carbon fiber, velomobiles prioritize aerodynamics, comfort, and functionality. Their enclosed design shields riders from weather, making them suitable for year-round use, while their three-wheel stability and ergonomic seating enhance comfort and ease of handling. The aerodynamic structure reduces energy demands, ensuring efficiency even in stop-and-go urban traffic. Beyond comfort and design, velomobiles contribute significantly to sustainability. They offer a zero-emission alternative to cars, reduce urban congestion, and promote physical fitness. With storage compartments for convenience, they address common limitations of bicycles. By making cycling safer and more appealing, velomobiles encourage a shift toward greener commuting, helping cities tackle pollution and climate challenges effectively.